Cost-effective Public Opinion Monitoring and Analysis Method and Device (Journal of Informatics Education and Research, 2023)
This research presents a method and device for monitoring and analyzing public opinion in a cost-effective manner. The proposed method involves acquiring public opinion data from website servers on the internet, which includes valuable asset information. It also includes receiving acquisition requests from clients and extracting application requirements and client identifiers from these requests. The method further involves screening the asset information in the public opinion data based on the application requirements to obtain targeted public opinion data that matches the specified criteria. Finally, the method transmits the filtered public opinion data to the respective clients using client identifiers. This approach addresses the problem of high hardware costs and internet resource wastage associated with existing public opinion monitoring and analysis systems.